2009
DOI: 10.1524/zpch.2009.6084
|View full text |Cite
|
Sign up to set email alerts
|

Li Ion Diffusion in Nanocrystalline and Nanoglassy LiAlSi2O6 and LiBO2 - Structure-Dynamics Relations in Two Glass Forming Compounds

Abstract: In the present study the Li diffusivity in nanostructured samples of two glass forming model systems, spodumene (LiAlSi 2 O 6 ) and lithium metaborate (LiBO 2 ), was examined using 7 Li nuclear magnetic resonance (NMR) spin-lattice relaxometry and dc conductivity measurements. The nanostructured samples were prepared by high-energy ball milling of the respective crystalline starting material on the one hand and the corresponding glass on the other hand. The diffusivity of the glass exceeds that of the crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 65 publications
(86 reference statements)
3
18
0
Order By: Relevance
“…In nanocrystalline ionic conducting ceramics, the increased concentration of interfacial regions may form percolation pathways for fast ion diffusion, resulting in more obviously enhanced conductivity compared to those with microsize grains . Examples in this concern are mainly the model systems with single phase such as LiBO 2 , LiAlSi 2 O 6 , LiNbO 3 , or LiTaO 3 . The discovery of interfacial fast lithium‐ion diffusion opens up a route for improving the conductivity of oxide electrolytes.…”
Section: Historical Perspectivementioning
confidence: 99%
“…In nanocrystalline ionic conducting ceramics, the increased concentration of interfacial regions may form percolation pathways for fast ion diffusion, resulting in more obviously enhanced conductivity compared to those with microsize grains . Examples in this concern are mainly the model systems with single phase such as LiBO 2 , LiAlSi 2 O 6 , LiNbO 3 , or LiTaO 3 . The discovery of interfacial fast lithium‐ion diffusion opens up a route for improving the conductivity of oxide electrolytes.…”
Section: Historical Perspectivementioning
confidence: 99%
“…At first glance one would expect no significant influence when an already disordered material is milled. So far only few reports, however, showed that high-energy ball-milling of glassy materials ( LiAlSi 2 O 6 (β-spodumene, [105]), LiBO 2 [20,106]) results in a decrease of the ionic DC conductivity, see also Ref. [107].…”
Section: Glass Formers: the Influence On Ball Milling On Ion Transpormentioning
confidence: 99%
“…Due to the fast ionic conduction property, lithium metaborate has a number of potential applications in advanced materials with controlled chemical and new physical properties such as lithium ion batteries, electrochromic displays, gas sensors, etc [1,72,134]. Recently, experimental studies on ion transport and diffusion in nanocrystalline and glassy ceramics of LiNbO 3 , LiAlSi 2 O 6 and LiBO 2 using the measurement of dc conductivities and 7 Li nuclear magnetic resonance spin-lattice relaxation rates have been performed [72,73]. Their measured activation energy for the Li + ion long-range transport as derived from the dc conductivity in LiBO 2 (with α-LiBO 2 as the majority phase) is 0.80-0.71 eV when going from the microcrystalline via the nanocrystalline to the glassy state, whereas the activation energy for the short-range Li + ion migration obtained from the spin-lattice relaxation rates is 0.23-0.21 eV when going from the nanocrystalline to the glassy state.…”
Section: Defects and Diffusion In Libo 2 Bulkmentioning
confidence: 99%